The Evolution of Financial Technology in Indonesia - Albert Manawar; Chandra Lukita; Lista Meria (Pandawan Sejahtera Indonesia, 2023)
Financial technology has its origins in industrialized nations with well-established infrastructure, cutting-edge technology, and a more digitally-oriented populace. Fintech has had trouble entering poor countries and enhancing their financial inclusion, even if this is not the case for emerging nations. This study attempts to identify global fintech best practices and examine how they could enhance the economic well-being of those living in poor nations. We categorized the issues into three categories: a lack of infrastructure, a society that is less digital, and an unorganized and informal culture. Then we looked at Microfinancing, Crowdfunding, Digital payment system as the three fintech’s that best embody the three categories. The development of financial technology began in industrialized countries with advanced infrastructure, cutting-edge technology, and a population that was more accustomed to using digital devices. Even while this is not the case for rising countries, fintech has difficulty reaching poor countries and improving their financial inclusion. This study looks for global fintech best practices and considers how they could improve the economic security of people in developing countries. We divided the problems into three groups: a dearth of infrastructure, a society that uses less technology, and an unstructured and disorganized culture. The three fintech’s that most closely represent the three categories were then examined: Micro Financing, Crowdfunding, Digital payment system.